Bibliometric Analysis: Trends and Patterns of Islamic Studies Theories and Methods in The Last Five Years - Agus Faisal Asyha; Yeni Astuti; Ahmad Faisol Ansori; Sudarman (Fakultas Agama Islam Universitas Billfath, 2025)
This study aims to analyze trends, citation patterns, and collaborations in research related to the theory and methods of Islamic Studies over the past five years to provide an in-depth understanding of the development of theory and methods in Islamic Studies, identify significant contributions from journals, researchers, and institutions, and uncover research gaps that could be opportunities for further development. The bibliometric method used includes collecting data from Google Scholar using the Publish or Perish application, which is then visualized with VOSviewer software to analyze collaboration patterns, publication trends, and citation networks. The study also integrates quantitative and qualitative analysis to provide a richer interpretation of the data. The results show that publications in Islamic Studies experienced a significant increase in 2023 with the highest number of studies, although there was a decline in 2024. Other key findings include the dominance of traditional methods such as interpretation in research, although contemporary approaches such as phenomenology and comparative methods continue to evolve. However, there are gaps in cross-disciplinary integration and broader international collaboration. The novelty and contribution of this research lies in its comprehensive approach in combining bibliometric methods and qualitative analysis to map the development of Islamic Studies theory and methods, as well as identifying unanswered research gaps. The study not only provides insight into the latest scientific trends and patterns but also offers strategic recommendations to improve the quality and relevance of research in this field in the future.